Mythical Association of Male Body in Baahubali Series - Thapa, Kalpana (Interdisciplinary Journal of Innovation in Nepalese Academia, 2022)
This study entitled as “Mythical Association of Male Body in Baahubali Series” explores how S.S. Rajamauli destabilizes the cinematic convention of the constructed female body in consideration of the male gaze in the Bollywood film industry. It investigates the entertainment industry’s presentation of the male body for both the male and female gaze in Baahubali Series. Moreover, the manuscript highlights the glorification of the male body through rigorous training and constant maneuver in resonance with the Eastern mythologies and Hindu scriptures. The study discovers the reworking of myth and archetype in film and an ideal male body prepared in gym centers and training institutions. Cinematic representations of Bhima, Krishna, Lord Vishnu and Arjuna mythologize male bodies. The research paper examines the texts from the perspectives of Body Studies and the body myth from the Eastern epic traditions, including Mahabharata, Ramayana and Hindu hymns. Similarly, the body of Baahubali rehearses Bhima and Krishna, the body of Bhalla Deva with Duryodhana and the body of Bajjala Deva with Dhritarastra. The Hollywood film industry’s projection of the body with resonance of myth and archetype subverts the traditional notion of body as impure trivial thing. Since the representation of the body in Bollywood movies has barely been explored, this study can be significant source for the researchers of myth, movie and masculinity in the future.